2019
DOI: 10.3390/catal9080631
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Electrocatalytic Behaviour of Poy(aniline-co-2-hydroxyaniline) Coated Electrodes for Hydrogen Peroxide Electrooxidation

Abstract: Polymer-coated electrodes are widely used for the detection and oxidation of hydrogen peroxide (H 2 O 2 ). Conducting polyaniline (PANI), poly (2-hydroxyanilne) (PHA), and their copolymer poly(aniline-co-2-hydroxyaniline) (PACHA) were electrochemically synthesized on a gold substrate for H 2 O 2 detection and analysis. Cyclic voltammetry (CV), square wave voltammetry (SWV), and differential pulse voltammetry (DPV) techniques were used for electroanalysis. Both PACHA and PANI greatly reduced the gold overpotent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Other reports regarding the sensitive detection of other analytes through CV have been presented elsewhere. [34][35][36] Effect of electrolyte.-Three electrolytes, acetate buffer, phosphate buffer and Britton Robinson buffer (BRB) were tested for selecting electrolyte with the best choice in order to get best shaped voltammogram with highest peak current for determination of TPTH. According to Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Other reports regarding the sensitive detection of other analytes through CV have been presented elsewhere. [34][35][36] Effect of electrolyte.-Three electrolytes, acetate buffer, phosphate buffer and Britton Robinson buffer (BRB) were tested for selecting electrolyte with the best choice in order to get best shaped voltammogram with highest peak current for determination of TPTH. According to Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The electrochemical behavior reduction or and oxidation [29,30] of NiCl2 was studied at different temperatures (293.15, 303.15, and 313.15K) in the presence of potassium ferrioxalate as mediators in 0.1 M citric acid since normally nickel ions gave no waves in acidic media. This method is simple to discuss the electrochemical behavior of Ni(II) ions.…”
Section: Resultsmentioning
confidence: 99%
“…When studying electrooxidation of methanol in basic media, it is assumed that hydroxyl ions, methanol, and gold are the responsible species for the oxidation process. During the methanol oxidation reaction in basic media, hydroxyl ions produce abundantly, which are strongly adsorbed by the gold electrode surface by producing numerous gold oxide ions, which then make way for methanol oxidation [36]. It is also observed that there is continuous peak shift towards negative potential with the increase in methanol concentration, which means that oxidation of methanol on PACHA coated gold electrodes is a diffusion controlled phenomenon [26,58] or may also be due to oxide layer formation [36].…”
Section: Electro Oxidation Of Methanol On Pacha Coated Goldmentioning
confidence: 99%
“…During the methanol oxidation reaction in basic media, hydroxyl ions produce abundantly, which are strongly adsorbed by the gold electrode surface by producing numerous gold oxide ions, which then make way for methanol oxidation [36]. It is also observed that there is continuous peak shift towards negative potential with the increase in methanol concentration, which means that oxidation of methanol on PACHA coated gold electrodes is a diffusion controlled phenomenon [26,58] or may also be due to oxide layer formation [36]. Elsewhere electrooxidation of 1 M methanol in 0.5 M NaOH was reported around −0.1-0.2 V on pladium-polyaniline coated gold electrodes [52].…”
Section: Electro Oxidation Of Methanol On Pacha Coated Goldmentioning
confidence: 99%
See 1 more Smart Citation